2021
DOI: 10.3390/nano11051096
|View full text |Cite
|
Sign up to set email alerts
|

The Heating Efficiency and Imaging Performance of Magnesium Iron Oxide@tetramethyl Ammonium Hydroxide Nanoparticles for Biomedical Applications

Abstract: Multifunctional magnetic nanomaterials displaying high specific loss power (SLP) and high imaging sensitivity with good spatial resolution are highly desired in image-guided cancer therapy. Currently, commercial nanoparticles do not sufficiently provide such multifunctionality. For example, Resovist® has good image resolution but with a low SLP, whereas BNF® has a high SLP value with very low image resolution. In this study, hydrophilic magnesium iron oxide@tetramethyl ammonium hydroxide nanoparticles were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Comparatively, for the bionized nanoferrite (BNF ® ) commercial nanoparticles prepared via the core-shell method with a core of Fe 3 O 4 and a shell of dextran or hydroxyethyl starch, having a nanoparticle size of 14 nm (close to that of our sample (16 nm)), and for a magnetic field of 9.5 kA/m and a frequency of 614.4 kHz, an ILP of 0.25 nH•m 2 /kg was obtained [48]. This value is significantly lower than the one obtained in the case of our sample (1.43 nH•m 2 /kg).…”
Section: Sample/ Concentration Cell Viability (%) Of Mcf-7mentioning
confidence: 67%
See 1 more Smart Citation
“…Comparatively, for the bionized nanoferrite (BNF ® ) commercial nanoparticles prepared via the core-shell method with a core of Fe 3 O 4 and a shell of dextran or hydroxyethyl starch, having a nanoparticle size of 14 nm (close to that of our sample (16 nm)), and for a magnetic field of 9.5 kA/m and a frequency of 614.4 kHz, an ILP of 0.25 nH•m 2 /kg was obtained [48]. This value is significantly lower than the one obtained in the case of our sample (1.43 nH•m 2 /kg).…”
Section: Sample/ Concentration Cell Viability (%) Of Mcf-7mentioning
confidence: 67%
“…However, in the same magnetic field conditions (9.5 kA/m and 614.4 kHz), Darwish et al [48] reported for ILP a value of 3.8 nH•m 2 /kg for core-shell nanoparticles of magnesium iron oxide@tetramethyl ammonium hydroxide (MgIONPs@TMAH), having a size of 15 nm. Moreover, Nishimoto et al [49] reported an ILP value of ~2 and ~4 for commercial Resovist ® and MEADM-033-02 nanoparticles, which are γ-Fe 2 O 3 nanoparticles coated with carboxydextran and carboxymethyl-diethylaminoethyl dextran, respectively, having a size of 5-6 nm and a concentration of 2 mg-Fe/mL, for a magnetic field of 4 kA/m and 100 kHz.…”
Section: Sample/ Concentration Cell Viability (%) Of Mcf-7mentioning
confidence: 95%
“…These MNPs can be used as a dual‐functional tracer in both high‐performance hyperthermia therapy and functionalized imaging for theragnosis. [ 274 ]…”
Section: Imaging For Vascular Abnormalitymentioning
confidence: 99%
“…Over the last few years, there has been considerable work designing MPI- and hyperthermia-tailored SPIONs with high resolution and sensitivity, as well as efficient heating performance. 13,326 Generally, for better heating characteristics, SPIONs should have colloidal stability, phase purity, a narrow size distribution, and optimal magnetic properties. 327 In a recent study, Bleul et al demonstrated the use of a micromixer synthesis platform (Fig.…”
Section: Primary Biomedical Applications Of Mpimentioning
confidence: 99%